Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1055/s-0043-125318
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostik und Therapie vesikovaginaler und ureterovaginaler Fisteln

Abstract: Industrial and developing countries continue to display significant differences in the etiology of fistulas as well as the operative treatment. The therapeutic concepts in place exhibit high success rates irrespecitve of the surgical approach and should be individually developed in accordance with the etiology, location and size of the fistula as well as the condition of the surrounding tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Different authors reported the use of both dyes for diagnostic procedures including: in vivo confocal laser endomicroscopy [37,38], in vivo microscopy to identify Barrett's esophagus [39], pathological changes in oral mucosa [40], colon [9], stomach [41], duodenum, upper gastrointestinal tract [41] and central airway, cervical tissue [35,42], cervix [35], sarcoma [43], urinary fistula [44], sentinel node (SN)'s, head and neck cancers [45], breast cancer [17], and gastrointestinal and thyroid surgery [10]. Apart from MB and PRO's ability to stain nuclei, the latter also stains non-specifically the membranes of adipocyte cells, making it possible to identify adipocytes without using a contrast agent [43].…”
Section: Preoperative and Intraoperative Use In Cardiac Surgerymentioning
confidence: 99%
“…Different authors reported the use of both dyes for diagnostic procedures including: in vivo confocal laser endomicroscopy [37,38], in vivo microscopy to identify Barrett's esophagus [39], pathological changes in oral mucosa [40], colon [9], stomach [41], duodenum, upper gastrointestinal tract [41] and central airway, cervical tissue [35,42], cervix [35], sarcoma [43], urinary fistula [44], sentinel node (SN)'s, head and neck cancers [45], breast cancer [17], and gastrointestinal and thyroid surgery [10]. Apart from MB and PRO's ability to stain nuclei, the latter also stains non-specifically the membranes of adipocyte cells, making it possible to identify adipocytes without using a contrast agent [43].…”
Section: Preoperative and Intraoperative Use In Cardiac Surgerymentioning
confidence: 99%